Quantum type indeterminacy in dynamic decision-making: Self-control through identity management - Ariane Lambert-Mogiliansky; Jerome Busemeyer (Games, 2012)
The Type Indeterminacy model is a theoretical framework that uses some elements of quantum formalism to model the constructive preference perspective suggested by Kahneman and Tversky. In a dynamic decision context, type indeterminacy induces a game with multiple selves associated with a state transition process. We define a Markov perfect equilibrium among the selves with individual identity (preferences) as the state variable. The approach allows to characterize generic personality types and derive some comparative static results.
Keywords: D03; D81; C73; 330; indeterminacy; decision-making; self-control; identity